(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to evaluate the degree of sleep disorders and examine the relationship between sleep quality and family function in patients visiting Thanh Nhan Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 75 patients aged 18 and older, managed and treated at the Endocrinology Clinic of Thanh Nhan Hospital from February to May 2024. Inclusion criteria included patients with insomnia, hypersomnia, sleep-onset disorders and sleep rhythm disorders; living with at least 2 family members. Data were collected using PSQI questionnaire to assess sleep quality and the APGAR index to evaluate family function. Data analysis was performed with SPSS 20.0 software. Results: Among the 75 participants, the majority experienced mild sleep disorders (46.67%), moderate sleep disorders (44%), and a few severe sleep disorders (9.33%). Common issues included nocturia (90.82%), loud snoring and coughing (30.9%) and pain (20.38%). Results also showed a correlation between the severity of sleep disorders and family function: patients with higher APGAR scores demonstrated better sleep quality. Those with severe sleep disorder were more likely to have poor family function (42.9%), meanwhile the patients with mild and moderate sleep disorders showed better family function. Conclusion: The sleep quality of patients at Thanh Nhan Hospital in 2024 was generally poor, with over half significant experiencing moderate to severe sleep disorders. There is an association between family function and the degree of sleep disorders. Strong family function contributes to improved sleep quality, while poor family function increases the degree of sleep disorders.